Managing Risks in Education Insurance with Tabarru' Funds at PT Takaful Keluarga - Awalia, Rabiatul; Maulidizen, Ahmad (Tatar Pasundan: Jurnal Diklat Keagamaan, 2024)
Risk management is crucial in the insurance industry, especially in managing tabarru' funds for education insurance. PT Takaful Keluarga, a company specializing in family and education insurance, faces challenges that may affect its operational stability and sustainability. This study examines the risk management practices applied by PT Takaful Keluarga in managing education insurance tabarru' funds. Using a descriptive qualitative approach, the research gathers data through interviews, participatory observations, and document analysis. The findings show that PT Takaful Keluarga has implemented a holistic risk management strategy, which includes risk identification, evaluation, and mitigation. Identified risks include fluctuations in financial markets, regulatory changes, and high claim risks. The company mitigates investment risks through diversification and financial instruments, while strict underwriting policies are used to manage claim risks. Keywords: risk management; takaful insurance; tabarru' fund; educational insurance; risk mitigation strategies